2004
DOI: 10.2333/bhmk.31.99
|View full text |Cite
|
Sign up to set email alerts
|

The Facets of Criminality: A Cross-Modal and Cross-Gender Validation

Abstract: In order to establish if criminals carried out distinct sub-sets of criminal activity as opposed to being widely versatile in the type of crime that they committed, 54 female and 49 male offenders completed a self-report questionnaire that asked about their criminality in two modes: Convictions and actual commission. MDS analysis of the resulting data supported the hypothesis that there is a subset of general criminal activities that most offenders have been involved in, but that there is also a tendency for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Empirical evidence suggests this construct does not present a unifactorial structure. Recent publications refer to antisocial behaviour as a variable that groups distinct types of acts (Carter, Gray, Baillargeon & Wakschlag, 2013;Farrington, 2005;Russell & Odgers, 2016;van Lier, Wanner & Vitaro, 2007;Youngs, Canter & Cooper, 2004), and these findings were corroborated here.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Empirical evidence suggests this construct does not present a unifactorial structure. Recent publications refer to antisocial behaviour as a variable that groups distinct types of acts (Carter, Gray, Baillargeon & Wakschlag, 2013;Farrington, 2005;Russell & Odgers, 2016;van Lier, Wanner & Vitaro, 2007;Youngs, Canter & Cooper, 2004), and these findings were corroborated here.…”
Section: Discussionsupporting
confidence: 85%
“…37(1) / pp. 13-27 / 2019 / ISSNe2145-4515 2005; Youngs et al, 2004). Antisocial behaviour tends to be more frequent in males than in females (Eme, 2015), except when it is related to drug use (Kennedy, Epstein, Phillips & Preston, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Second, a self-report questionnaire allows fuller description of the psychological and contextual qualities of the behaviours than do official data. Third, a previous study by Youngs, Canter, and Cooper (2004) with a version of the questionnaire used in the present study, obtained with the questionnaire, results similar to those found from official records.…”
Section: The Self-report Methodologysupporting
confidence: 78%
“…In offender populations specifically, studies have uncovered meaningful thematic elements underlying several types of crimes (Bennell and Canter, 2002; Santtila et al , 2003; Trojan and Salfati, 2008; Alison, 2005; Youngs et al , 2004). For example, studies have distinguished between offenses motivated by expressive‐affective and those motivated by instrumental forms of aggression (Salfati and Park, 2007).…”
Section: Introductionmentioning
confidence: 99%